2003
DOI: 10.1098/rspb.2002.2280
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mating and sequential mate choice in guppies: females trade up

Abstract: The trade-up hypothesis outlines a behavioural strategy that females could use to maximize the genetic benefits to their offspring. The hypothesis proposes that females should be more willing to accept a mate when the new male encountered is a superior genetic source to previous mates. We provide a direct test of the trade-up hypothesis using guppies (Poecilia reticulata), and evaluate both behavioural and paternity data. Virgin female guppies were presented sequentially with two males of varying attractivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
187
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(196 citation statements)
references
References 52 publications
8
187
0
1
Order By: Relevance
“…However, once mated, females may become less receptive in subsequent matings, either as a result of male manipulation via products in the seminal fluid that inhibit re-mating [48] or because females become more discriminating after securing an adequate supply of sperm [49][50][51]. In the context of the reproductive biology of C. scorpioides females, male suppression of female re-mating would be highly adaptive even in the absence of last male sperm precedence.…”
Section: Discussionmentioning
confidence: 99%
“…However, once mated, females may become less receptive in subsequent matings, either as a result of male manipulation via products in the seminal fluid that inhibit re-mating [48] or because females become more discriminating after securing an adequate supply of sperm [49][50][51]. In the context of the reproductive biology of C. scorpioides females, male suppression of female re-mating would be highly adaptive even in the absence of last male sperm precedence.…”
Section: Discussionmentioning
confidence: 99%
“…In the wild, females can be subjected to up to one sneaky mating attempt per minute (Magurran & Seghers 1994), which may account for the high levels of multiple paternity reported in natural guppy populations (Neff et al 2008). Both the intensity of the male's courtship displays and the area of orange in the male's colour patterns have been shown to be positively phenotypically correlated with ejaculate quality (Matthews et al 1997;Locatello et al 2006;Pitcher et al 2007; but see Skinner & Watt 2006), and these relationships are thought to explain why sperm competition favours males with relatively high levels of orange (Evans et al 2003;Pitcher et al 2003) and correspondingly high levels of courtship (Evans & Magurran 2001). However, females also differentially retain (or reject) ejaculates according to their perception of male attractiveness (Pilastro et al 2004), and therefore the positive association between male sexual attractiveness and paternity success (Evans & Magurran 2001;Evans et al 2003) may be influenced by female-mediated processes that favour relatively attractive males in sperm competition (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies indicate that male phenotype covaries with sperm load (Matthews et al 1997;Pilastro & Bisazza 1999;Pitcher & Evans 2001) and that males with preferred phenotypes are likely to be favoured during post-copulatory sexual selection (Pilastro & Bisazza 1999;Evans & Magurran 2001;Pilastro et al 2002;Evans et al 2003; see also Pitcher et al 2003). Evans and Magurran (2000) found that offspring from multiply mated female guppies exhibited enhanced schooling abilities and better developed anti-predator escape responses than their singly sired counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mating by females, which is common in guppies (Constantz 1984;Kelly et al 1999;Evans & Magurran 2000;Pitcher et al 2003), extends the opportunity for sexual selection beyond copulation (Jennions & Petrie 2000;Fedorka & Mousseau 2002). Indeed, studies indicate that male phenotype covaries with sperm load (Matthews et al 1997;Pilastro & Bisazza 1999;Pitcher & Evans 2001) and that males with preferred phenotypes are likely to be favoured during post-copulatory sexual selection (Pilastro & Bisazza 1999;Evans & Magurran 2001;Pilastro et al 2002;Evans et al 2003; see also Pitcher et al 2003).…”
Section: Introductionmentioning
confidence: 99%